Integrating Free-Range Hens into a Wheat Stubble - Miao, Z.H.; Glatz, P.C.; Ru, Y.J.; Wyatt, S.K.; Rodda, B.J. (International Journal of Poultry Science, 2005)
Some grain farmers, market gardeners and graziers integrate hens into their farming system in Australia. In this system, hens move freely around the farm except that they are usually locked in sheds at night for protection from predators. Consumers pay a premium for eggs due to enhanced welfare of hens in a free-range system. The purpose of this experiment was to compare the impact of hens vs. sheep when integrated into a wheat stubble in a crop and pasture rotation system. The stubble availability, weeds and soil fertility were measured before and after grazing. Laying hens stocked at 110/ha (compared to the sheep stocking density of 12/ha) were allowed to forage on the wheat stubble. The performance of the free-range hens was excellent with production averaging 90%. Free-range hens were heavier than Hyline standard (2.09 vs. 1.99 kg) at week 33. Hens foraged extensively in the wheat stubble over the foraging period from January to May. Generally, paddocks foraged by hens had more stubble remaining compared to paddocks grazed by sheep. Hens preferred rye seeds, while sheep preferred other grass, wire weed, medic pods and other broad leaf weeds. There was no effect of grazing on soil pH with this low stocking density of both sheep and hens but soil nitrate levels were higher (6.69 vs. 39.90 mg/L for sheep and 7.80 vs. 32.98 mg/L for hens) after grazing, suggesting that animal droppings were contributing to the increase. This trial indicates that integrating hens into crop and pasture rotation system could assist in weed control and increase soil fertility.